Evaluation of the ResistancePlus GC (beta) assay: a commercial diagnostic test for the direct detection of ciprofloxacin susceptibility or resistance in Neisseria gonorrhoeae. (20th March 2019) - Ebeyan, Samantha; Windsor, Madeline; Bordin, Amanda; Mhango, Lebogang; Erskine, Simon; Trembizki, Ella; Mokany, Elisa; Tan, Lit Yeen; Whiley, David; ,
Abstract: Objectives: To evaluate the performance of the ResistancePlus GC (beta) assay for the simultaneous detection of Neisseria gonorrhoeae and gyrA S91 markers of resistance (S91F) and susceptibility (WT) to ciprofloxacin, from both clinical specimens and isolates. Methods: Performance was assessed on several sample banks, including N. gonorrhoeae isolates ( n = 822), non-gonococcal isolates ( n = 110), N. gonorrhoeae -positive clinical specimens ( n = 402) and N. gonorrhoeae- negative specimens ( n = 290). Results were compared with previous testing data, including S91 genotyping and phenotypic resistance profiles. Results: Overall, the assay demonstrated 100% sensitivity for N. gonorrhoeae detection in clinical isolates. For gyrA S91 mutation detection in clinical isolates, the assay showed 100% sensitivity/specificity compared with the genotype, and >99%/>97% sensitivity/specificity when compared with phenotype. For positive clinical specimens, the assay demonstrated >96% sensitivity for N. gonorrhoeae detection and 100% sensitivity/specificity for gyrA S91 mutation detection. The assay demonstrated >99% specificity for N. gonorrhoeae detection against non-gonococcal isolates and 100% specificity for negative clinical specimens. Conclusions: The ResistancePlus GC (beta) assay is suitable for the detection of N. gonorrhoeae and gyrA markers associated with resistance/susceptibility to ciprofloxacin directly in clinical samples. This assay could be implemented for the individualized treatment of gonorrhoea infections as well as to enhance current antimicrobial resistance surveillance methods.